Eco-friendly antimicrobial finishing of cotton fabrics using bioactive agents from novel Melia azedarachayan berries extract and their performance after subsequent washings - Murtaza Haider, Syed; Syed, Qutaba; Mior Ahmad Khushairi, Mohd Zahari; Norhayati, Abdullah; Shoaib, Muhammad; Bashir, Hafiza Fareeha; Ali, Muhammad Qasim; Ali, Ramzan; Iqbal, Ahsan; Wajid, Ali (Egyptian Journal of Chemistry, 2023)
Fabrics with antibacterial assets have become essential to organize and manage the infestation by microbes and to reduce the formation of odor. The fabrics with antimicrobial finishes are subjected to subsequent washings and their effectiveness after each wash is of prime concern when consumed by human beings. Cotton fabric has large advantages such as compatibility, absorbency, good dimensional stability, and lower shrinkage. One of their major draw backs is that their degradation occurs due to the bacteria on them. In order to evaluate antimicrobial activity, we have prepared natural and organic extracts from peels of wild tree Melia azedarachayan (common name Bakaayan) plant berry. The Bakaayan berries were kept in the ethyl acetate for two weeks and a pitch of berry was obtained through the distillation process and applied to the fabric by padding and anti-microbial activities were analyzed after 24 hours by studying bacteria growth on the fabric.After analyzing bacterial growth on fabric by microscope the extracted pitch was found as antimicrobial. In a study, the fabric samples were tested for antimicrobial activity against bacterial strains like Staphylococcus, E. coli, Bacillus, C. albicans under qualitative and quantitative analysis. The results of the study have indicated that the cotton fabric shows a better microbial resistance against the above-mentioned strains except for C. albicans. As per quantitative analysis, the fabric treated with antimicrobial extract showed the best reduction against Staphylococcus. For analyzing the effect of washing on antimicrobial activity; the finished fabrics were washed according to the standard ISO 6330. The washing result shows a gradual decrease in antimicrobial activity after each wash.